Copper nanoparticles mediated by chitosan: synthesis and characterization via chemical methods - Usman, Muhammad Sani; Ibrahim, Nor Azowa; Shameli, Kamyar; Zainuddin, Norhazlin; Wan Yunus, Wan Md. Zin (MDPI, 2012)
Herein we report a synthesis of copper nanoparticles (Cu-NPs) in chitosan (Cts) media via a chemical reaction method. The nanoparticles were synthesized in an aqueous solution in the presence of Cts as stabilizer and CuSO4·5H2O precursor. The synthesis proceeded with addition of NaOH as pH moderator, ascorbic acid as antioxidant and hydrazine as the reducing agent. The characterization of the prepared NPs was done using ultraviolet-visible spectroscopy, which showed a 593 nm copper band. The Field Emission Scanning Electron Microscope (FESEM) images were also observed, and found to be in agreement with the UV-Vis result, confirming the formation of metallic Cu-NPs. The mean size of the Cu-NPs was estimated to be in the range of 35–75 nm using X-ray diffraction. XRD was also used in analysis of the crystal structure of the NPs. The interaction between the chitosan and the synthesized NPs was studied using Fourier transform infrared (FT-IR) spectroscopy, which showed the capping of the NPs by Cts.